A Review of the Effect of Social Capital on Human Development in Iran - Razmi, Mohammad Javad; Bazazan, Sahar Sherkat (International Journal of Economics and Financial Issues, 2012)
The present study aims to investigate the effect of social capital on human development in Iran. For this purpose, Iran society in the period 1984 to 2009 by using time series data and Autoregressive Distributed Lags (ARDL) technique has been studied. Due to the quality of social capital variable two variables i.e. the number of judicial cases related to nonsufficient fund checks and embezzlement, bribery and forgery, and elections' participation rate have been used to measure the effect of social capital. The results suggest that there is a negative and significant effect of judicial cases on human development index (HDI) level and elections' participation index statistically has not significant effect on Iran's human development index. Keywords: Social Capital; Human Development; ARDL Technique; Iran; Embezzlement; Forgery; Financial crimes JEL Classifications: O14